Penerapan Metode Scramble dalam Pembelajaran Pendidikan Agama Islam pada Fase F di Sekolah Menengah Atas Negeri 4 Tambusai Utara - Sugiat, Sugiat; Nurulazmi, Nurulazmi (Medan Resource Center, 2024)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character, morals, and spirituality, necessitating appropriate teaching methods to achieve optimal learning outcomes. Teachers must select instructional strategies that align with students' needs to foster an engaging and effective learning environment. One such method is the scramble learning method, which was implemented in this Classroom Action Research (CAR) study conducted at SMA Negeri 4 Tambusai Utara for Phase F students. This research employed a qualitative descriptive field study approach, utilizing observations, interviews, and documentation as data collection techniques. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the scramble method was effective, following the prescribed stages. This method created a dynamic and enjoyable learning atmosphere, enhancing student engagement, reducing fatigue, and increasing participation. Consequently, students remained attentive and motivated, leading to optimal learning outcomes. These results underscore the effectiveness of interactive and engaging teaching methods in Islamic Religious Education, emphasizing the need for teachers to adopt innovative approaches that align with contemporary pedagogical needs.